Fluctuation Patterns Spodoptera frugiperda and Its Natural Enemies on Maize Plants With IPM and Conventional Practice in Malang Regency - Prayogo, Bagas Agung; Mudjiono, Gatot; Widjayanti, Tita (Journal of Tropical Plant Protection, 2022)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is a pest that originated in the United States and then migrated to Indonesia. This pest reportedly attacked corn in West Pasaman, West Sumatra Province, in 2019. This study aimed to determine the effect of cultivation practice on fluctuations in natural enemies and S. frugiperda. The research was conducted in Pandan Rejo Village, Pagak, Malang Regency. Data from observations of pest populations' natural enemies were then analyzed using simple quantitative analysis. The population and intensity of Spodoptera frugiperda attacks on IPM practices were always lower than those on conventional practices. During observation, there were 2 species of natural enemies, Braconidae and Scelionidae. The parasitoid population in IPM is always higher than in conventional practice. The lower parasitoid population at conventional practice failed to suppress the S. frugiperda population. Farming business analysis calculated using the R/C ratio showed that IPM practice had a value of 1.03 while conventional was only 0.55. IPM practice is feasible and more ecologically friendly than conventional practice.